Effect of taxifolin on methotrexate-induced oxidative and inflammatory oral mucositis in rats: biochemical and histopathological evaluation (Journal of Applied Oral Science, 2022)
The role of oxidative stress, as well as inflammation in the pathogenesis of methotrexate (MTX)-induced oral mucositis, is a known fact. The anti-inflammatory, antitumor, antimicrobial, and antioxidant properties of taxifolin—the effect we tested against MTX-induced oral mucosal damage—are well known. Objective: Evaluating biochemically and histopathologically the effects of taxifolin on methotrexate-induced oral mucosal damage in rats. Methodology: In the taxifolin+MTX (TMTX) group, 50 mg/kg taxifolin was orally administered to rats by gavage. In the MTX and healthy (HG) groups, normal saline was applied to rats as solvent by the same method. One hour after administration of taxifolin and solvent, 5 mg/kg MTX was orally administered to rats in the MTX and TMTX groups. Taxifolin and methotrexate were administered once a day for 30 days. Macroscopic, biochemical, and histopathological evaluations were performed on the inner cheek and tongue tissues of rats. These parts were removed after rats were killed with a high-dose anesthesia. Results: Taxifolin with MTX prevented the increase in oxidant and pro-inflammatory parameters, such as malondialdehyde (MDA), tumor necrosis factor alpha (TNF-α), interleukin 1 beta (IL-1β), interleukin 6 (IL-6), on the inner cheek and tongue tissues of rats. Moreover, taxifolin antagonized the decrease in total glutathione (tGSH). Taxifolin decreased MTX-induced histopathological damage. Conclusion: These findings suggest that taxifolin may be useful to treat MTX-associated oral mucositis.